Hearing After Vestibular Schwannoma Surgery: Is It Preserved Forever?. Issue 3 (8th March 2023) - Fík, Zdeněk; Zverina, Eduard; Lisy, Jiri; Balatkova, Zuzana; Vlasak, Ales; Chovanec, Martin; Lazak, Jan; Tesarova, Michaela; Peterkova, Lenka; Betka, Jan
Abstract : Introduction: Currently, it is possible to preserve the auditory nerve in a large number of cases, but the preservation of the hearing itself is unpredictable. Apart from wait and scan strategy and stereoradiotherapy, hearing after vestibular schwannoma surgery is considered to remain stable even in long-term follow-up. Materials and Methods: Twenty-eight patients had preserved hearing after retrosigmoid suboccipital microsurgery of the vestibular schwannoma between 2008 and 2014. A standard audiological protocol was performed together with an magnetic resonance imaging evaluation of the fluid content of the inner ear. Results: The mean difference in pure-tone average between the direct and final postsurgical examination was 12.758 dB ( p = 2.5E − 06). The word recognition score deteriorated by 17.45% ( p = 0.03516). The mean American Academy of Otolaryngology–Head and Neck Surgery score on the second examination was 2.5, and that on the second examination was 3.111 ( p = 0.00483). There was no significant deterioration in the healthy ear. The signal intensity ratio in the basal turn of the cochlea increased by an average of 0.13 points ( p < 0.05). Patients with persistent tumor or nodular enhancement in the internal acoustic meatus deteriorated significantly in hearing according to the American Academy of Otolaryngology–Head and Neck Surgery scale compared with patients without any finding in the meatus ( p = 0.01299). Conclusions: There is a discrete but gradual deterioration of the hearing in the postoperative period. Hearing impairment is more pronounced in patients with a nodular process in the internal acoustic meatus, regardless of whether it is growth active. After surgery, the pathological content of the inner ear normalizes (evaluated on T2 magnetic resonance imaging sequences).